Shajarah: sustainable community living for Dubai's migrant labourers - Penhall, Robyn (My University, 2010)
Dubai’s blue-collar migrant workers, especially those working in the construction industry, are being exploited due to their desperate financial situations by lack of adequate permanent housing, poor working conditions and insufficient wages. Exploitation of a city’s poor working class for financial gain is a recurring result of rapidly expanding economies, despite the infringement of basic human rights. Dubai is no different. Although with past examples such as the 19th century Industrial Revolution in Europe and America, it is inexcusable that a 21st century city should be experiencing the same unjust labour practices as two-hundred years ago. Due to the immense development happening in Dubai, migrant labourers from Southeast Asia form the vast majority of the city’s blue-collar workforce, hoping to benefit from Dubai’s economic boom. However, because these poor migrant workers are seen as short-term labour to grow the city – their insignificant social status tolerated for the sake of the progress – their needs (especially with regard to housing) are largely ignored in favour of greater financial profits. They are forced to live in overcrowded and unsanitary squalor due not only to their desperate and helpless financial situations, but also due to lack of corporate conscience and government support. Dubai has been severely criticised by human rights organisations and the international media for its treatment of its blue-collar migrant workforce, and this is having an unanticipated effect of Dubai’s image as the rising ‘Mecca’ of trade and tourism in the Middle East. With more than 80% of the city’s population (over a million people) living in appalling poverty, the situation cannot be ignored for much longer. As a result, the purpose of this thesis is to investigate a sustainable, permanent and socially integrated alternative housing solution to challenge the existing overcrowded, substandard blue-collar migrant worker accommodation. SHAJARAH is a mixed-use community living housing project to challenge the existing overcrowded, substandard blue-collar migrant worker accommodation that has become such a controversial issue in the UAE. SHAJARAH can accommodate almost 30,000 people in a variety of room typologies to suit different needs, preferences and financial budgets. SHAJARAH offers residents a range of shared facilities, services and spaces to improve quality of life by supporting social interaction and environmental awareness. As the majority of developments in Dubai are aimed at the city’s wealthier residents, there is very little option for lower income groups in terms of affordable, quality accommodation. Although migrant labour contracts are usually only for a few years, SHAJARAH is envisaged as a long-term mixed-income development with constantly changing occupants, accommodating the present and future working classes that will sustain Dubai’s growing economy. Sustainable principles have been incorporated into its design, not only to protect the surrounding natural environment but to preserve the project’s long-term economic feasibility and foster improved social integration. By creating an urban development framework in which local and international architects can showcase their solutions to Dubai’s labour problem, SHAJARAH is helping to redefine the negative stigma attached to the conventional labour camp by creating an inclusive, vibrant community. It is only through the integration and co-operation of all sectors of society that Dubai can truly become the global contemporary city that it aspires to be.Besides, it is onl fairthat the peopleessentially responsible for building Dubai be afforded the same right to quality of life.